2016
DOI: 10.1002/hed.24639
|View full text |Cite
|
Sign up to set email alerts
|

ACR appropriateness criteria® nasal cavity and paranasal sinus cancers

Abstract: The American College of Radiology (ACR) Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer-reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
3
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 65 publications
3
29
3
8
Order By: Relevance
“…The dosimetric benefits of PT are widely accepted, allowing for increased doses to target volumes and reduced doses to surrounding normal tissues, resulting in a further decrease in toxicity. Studies have reported superior LC with PT over photon‐based RT, and as such guidelines recommend the consideration of PT for cases in which constraints to critical structures are not achievable with standard IMRT techniques . Given the rarity of this disease, comparing the outcomes of patients treated with photon‐based versus proton‐based RT is impossible within a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…The dosimetric benefits of PT are widely accepted, allowing for increased doses to target volumes and reduced doses to surrounding normal tissues, resulting in a further decrease in toxicity. Studies have reported superior LC with PT over photon‐based RT, and as such guidelines recommend the consideration of PT for cases in which constraints to critical structures are not achievable with standard IMRT techniques . Given the rarity of this disease, comparing the outcomes of patients treated with photon‐based versus proton‐based RT is impossible within a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…There are no randomized studies to guide management, and current treatment guidelines are based on observational studies and consensus opinion . Furthermore, interpretation of retrospective data is complex, as cancers of the nasal cavity are frequently analyzed with cancers of the paranasal sinuses, and most series include a variety of tumor histologies along with various disease stages.…”
Section: Introductionmentioning
confidence: 99%
“…For SCCs, locoregional control of 80% to 85% can be achieved following total resection and postoperative radiotherapy . Several retrospective series report that patients treated with surgery and radiation have better outcomes than patients treated with radiation alone, but such direct comparisons are hampered by selection bias, older radiotherapy techniques, which utilized inadequate doses of radiotherapy, and the inconsistent use of chemotherapy to enhance the effects radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of prospective randomized studies to lead clinical practice because of the rarity of this disease. The combination of resection, external beam radiotherapy, and systemic chemotherapy is an international standard treatment [2,3]. The National Comprehensive Cancer Network (NCCN) guidelines recommend elective nodal irradiation (ENI) for patients with T3 or T4 MSC, even in clinical node-negative (cN0) cases [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of ENI for MSC is controversial because of the variability in the frequency of regional failure of 3-33% [1], and the lack of reliable evidence. Furthermore, the long-term safety of ENI as a treatment for patients with advanced MSC is unknown due to its poor prognosis [3,4].…”
Section: Introductionmentioning
confidence: 99%